Local anaesthetics for regional and intra‐articular analgesia in the horse. (10th December 2019) - Schumacher, J.; Boone, L.
Summary: During the course of a lameness examination, intra‐articular or perineural administration of a local anaesthetic is often necessary to isolate the source of pain causing lameness. Local anaesthetics are useful for intraoperative and post‐operative pain relief and may allow for elimination of, or a decrease in, general anaesthesia. Within recent years, new information has become available concerning the use of local anaesthetics for localisation of pain and for palliation of pain. New information indicates that Lidocaine is less efficacious than mepivacaine or ropivacaine in ameliorating lameness caused by pain. After administering a nerve block, loss of skin sensation may not correlate with loss of pain causing lameness. Local anaesthetic solution must be deposited within the sheath of the neurovascular bundle to be effective. The dose of a local anaesthetic, which is a factor of volume and concentration, affects potency and duration of a nerve block. Local anaesthetics are toxic to chondrocytes and synoviocytes. Lidocaine and bupivacaine appear to be more toxic than mepivacaine or ropivacaine. The clinical significance of the toxic effect of a single intra‐articular injection of local anaesthetic is yet to be determined. Sodium bicarbonate can be added to a local anaesthetic solution to increase its potency and speed of onset. Epinephrine added to local anaesthetic solution prolongs and intensifies its analgesic effect. Mixing quick‐acting, short‐duration and slow‐acting, long‐duration local anaesthetics will not result in a quick‐acting, long‐duration drug combination.